OsPEX11, a Peroxisomal Biogenesis Factor 11, Contributes to Salt Stress Tolerance in Oryza sativa - Cui, Peng; Liu, Hongbo; Islam, Faisal; Li, Lan; Farooq, Muhammad A.; Ruan, Songlin; Zhou, Weijun (Frontiers in Plant Science, 2016)
Peroxisomes are single membrane-bound organelles, whose basic enzymatic constituents are catalase and H2O2-producing flavin oxidases. Previous reports showed that peroxisome is involved in numerous processes including primary and secondary metabolism, plant development and abiotic stress responses. However, knowledge on the function of different peroxisome genes from rice and its regulatory roles in salt and other abiotic stresses is limited. Here, a novel prey protein, OsPEX11 (Os03g0302000), was screened and identified by yeast two-hybrid and GST pull down assays. Phenotypic analysis of OsPEX11 overexpression seedlings demonstrated that they had better tolerance to salt stress than wild type and OsPEX11-RNAi seedlings. Compared with wild type and OsPEX11-RNAi seedlings, overexpression of OsPEX11 had lower level of lipid peroxidation, Na+/K+ ratio, higher activities of antioxidant enzymes (SOD, POD and CAT) and proline accumulation. Furthermore, qPCR data suggested that OsPEX11 acted as a positive regulator of salt tolerance by reinforcing the expression of several well-known rice transporters (OsHKT2;1, OsHKT1;5, OsLti6a, OsLti6b, OsSOS1, OsNHX1 and OsAKT1) involved in Na+/K+ homeostasis in transgenic plants under salinity. Ultrastructural observations of OsPEX11-RNAi seedlings showed that they were less sensitive to salt stress than wild type and overexpression lines. These results provide experimental evidence that OsPEX11 is an important gene implicated in Na+ and K+ regulation, and plays a critical role in salt stress tolerance by modulating the expression of cation transporters and antioxidant defense. Thus, OsPEX11 could be considered in transgenic breeding for improvement of salt stress tolerance in rice crop.